Penerapan Model Problem Based Learning untuk meningkatkan Kemampuan Berpikir Kritis Siswa Pada Materi Pendudukan Jepang dan Respon Bangsa Indonesia Kelas XI IPS MAN 4 Pandeglang - Nurhayati, Titing; Maryuni, Yuni; Fadillah, Moh. Ali (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
Application of the Problem Based Learning model to train students in improving critical thinking with the Japanese occupation material and the response of the Indonesian nation at MAN 4 Pandeglang. The goals to be achieved in this study are to gain knowledge about the effect of the Problem Based Learning model on students' critical thinking skills and to know the improvement of students' critical thinking skills by using the Problem Based Learning model. Quantitative is a research classification used in research with quasi-experiments as the research method. XI IPS 1 and XI IPS 2 samples used in this research apply the Problem Based Learning and Discovery Learning models. H0 is rejected and Hα is accepted according to the results of a one-sided t-test study, namely 2.07 > 1.67, which influences students' critical thinking skills. It can be concluded that the use of the Problem Based Learning model has an influence on students in the realm of critical thinking and the critical thinking skills of students who use the Problem Based Learning model in the experimental group get higher results than the control group with the Discovery Learning model. The average student score after the test in the experimental group was 83.80, then the average student score in the control group was 49.11.